What she wants - Roberts, Sheila, 1951- (Roberts, Sheila. 1951- Life in Icicle Falls., 2013)
What do women want? Jonathan Templar and his poker buddies can't figure it out. Take Jonathan, for instance. He's been in love with Lissa Castle since they were kids but, geek that he is, she's never seen him as her Mr. Perfect. He has one last shot<U+2014>their high school reunion. Kyle Long is equally discouraged. The pretty receptionist at his office keeps passing him over for other guys who may be taller but are definitely not superior. And Adam Edwards might be the most successful of Jonathan's friends, but he isn't having any success on the home front. His wife's kicked him out. When Jonathan stumbles on a romance novel at the Icicle Falls library sale, he knows he's found the love expert he's been seeking<U+2014>Vanessa Valentine, top-selling romance author. At first his buddies laugh at him for reading romance novels, but soon they, too, realize that these stories are the world's best textbooks on love. Poker night becomes book club night<U+2026>and when all is read and done, they're going to be the kind of men women want!